Power allocation for multi-point joint transmission with different node activeness - Jingya Li; Makki, Behrooz; Svensson, Tommy; Eriksson, Thomas (2013 IEEE Wireless Communications and Networking Conference (WCNC), 2013)
We study the power allocation problem for the downlink of a cooperative system with different node activeness, i.e., each receiving node requests for data transmission according to a certain probability. Data symbols of the active nodes are jointly transmitted from cooperative transmission points using zero-forcing precoding. The problem is cast in form of maximizing the ergodic achievable rate subject to per-transmit-point average total power constraints. The derived power allocation indicates that depending on the channel conditions and receiving nodes' activation probability, the optimal solution takes the form of either greedy power allocation or power sharing allocation.